2013
DOI: 10.1299/jbse.8.114
|View full text |Cite
|
Sign up to set email alerts
|

The Stabilization Effect of Mesenchymal Stem Cells on the Formation of Microvascular Networks in a Microfluidic Device

Abstract: There is a demand for three-dimensional (3D) angiogenesis model including endothelial cells (ECs) and mesenchymal stem cells (MSCs), which are known to differentiate into pericytes, to construct stabilized and matured microvascular networks in vitro. However, it remains to be elucidated how MSCs affected on ECs in the process of 3D angiogenesis. In this study, we utilized a microfluidic device to develop a 3D coculture system including human umbilical vein ECs and human MSCs, which allowed us to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…These ratios were selected based on pre-vious studies on EC-MSC coculture in two dimensional (2D) and 3D conditions. 7,26,27 In addition, in concordance with a previous study, the number of pericytes is comparable to or less compared with ECs in vivo. 28 Cells were cultured for 21 days in a 1:1 mixture of EGM-2 and MSC growth medium supplemented with 10 ng/mL bFGF and 10 ng/mL vascular endothelial growth factor (VEGF; R&D Systems, Minneapolis, MN).…”
Section: Huvec-msc Coculture In a Microfluidic Devicesupporting
confidence: 91%
See 3 more Smart Citations
“…These ratios were selected based on pre-vious studies on EC-MSC coculture in two dimensional (2D) and 3D conditions. 7,26,27 In addition, in concordance with a previous study, the number of pericytes is comparable to or less compared with ECs in vivo. 28 Cells were cultured for 21 days in a 1:1 mixture of EGM-2 and MSC growth medium supplemented with 10 ng/mL bFGF and 10 ng/mL vascular endothelial growth factor (VEGF; R&D Systems, Minneapolis, MN).…”
Section: Huvec-msc Coculture In a Microfluidic Devicesupporting
confidence: 91%
“…for 1 h to inhibit nonspecific staining. Cells were then incubated with primary antibodies, a mouse anti-a smooth muscle actin (aSMA) antibody (1:200 dilution, Clone 1A4; Sigma-Aldrich) for pericytes 29 or a rabbit anti-CD146 antibody 7 or a sheep anti-CD31 antibody (1:100 dilution; R&D Systems) for HUVECs, followed by incubation with secondary antibodies. These included the Alexa Fluor 488conjugated anti-mouse IgG (1:200 dilution; Invitrogen) or Alexa Fluor 594-conjugated anti-rabbit/sheep IgG (1:200 dilution; Invitrogen), respectively.…”
Section: Fig 1 Schematic Illustration Of a Microfluidic Device (A)mentioning
confidence: 99%
See 2 more Smart Citations
“…These MSCs became positive for α-SMA and eventually wrapped themselves around the forming vessels. Yamamoto et al (2013) reported that HUVEC-MSC direct contact was required for the differentiation of MSCs into pericytes in 2D culture. In this study, HUVEC-MSC coculture was also performed in a microfluidic device.…”
Section: Capillary Stabilization By Pericytes or Smcsmentioning
confidence: 99%